ANALISIS PENGARUH KOMPETENSI TENAGA PENJUALAN DAN KUALITAS PELAYANAN DALAM MEMBANGUN LOYALITAS PELANGGAN (Studi Kasus Outlet-Outlet Pelanggan PT. Sinar Majapahit Purwokerto) - Jati, Irawan Waluyo (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
Underlying the percentage of critic that is quite numerous about the sales force competency and service quality and noticing the decrease of the effective account that create the dissatisfaction of the customer outlets and then dropping the loyalty. Noticing this situation, PT. Sinar Majapahit needs to establish some efforts in order to maintain and to increase the number of its customers by giving more attention to the customer loyalty. Therefore, the purpose of this research is trying to answer of â€œHow to improve the customer loyalty.â€To answer the question, data is collected from 100 respondents that are consist of the customers of PT. Sinar Majapahit Purwokerto. They were asked to complete the questionnaires. Items of the questionnaires were purposively arranged in order to obtain the information about the sales force competency, service quality and customer loyalty. Then the data is analyzed using the multiple regression method.The result of the multiple regression method shows that the salesforce competency has a positive and significant impact on the loyalty of PT. Sinar Majapahit Purwokerto customers, service quality has a positive and significant impact on the loyalty of PT. Sinar Majapahit Purwokerto customers.